Determinants of online purchase intention: The role of live streaming shopping - Fendy Cuandra (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2022)
The live-streaming trend is increasingly widespread among Indonesian people, especially teenagers. This feature is widely used by sellers or e-commerce to promote their products and services to attract and increase consumer purchasing intention. Many factors affect consumer purchase intention using the live broadcast feature. Therefore, this study analyzes the factors influencing purchase intention: interactivity, media richness, technology acceptance models (perceived usefulness & perceived ease of use), perceived risk, and streamer's credibility. Data was collected using a questionnaire distributed online using a google form to 209 respondents in Batam City. This study revealed that interactivity, media richness, and perceived risk affect purchase intention. Meanwhile, perceived usefulness, ease of use, and streamer's credibility did not affect online consumer purchase intentions via live streaming shopping. This study is expected to help consumers in transactions using live-streaming shopping.